2009
DOI: 10.1186/1743-422x-6-108
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infection is highly prevalent among pregnant women in Accra, Ghana

Abstract: Consistent with similar studies worldwide, the results of our studies revealed a high prevalence of HEV infection in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 22 publications
5
53
13
Order By: Relevance
“…Our finding, though higher than 0% rate reported in a similar cohort in France [45], is lower than rates ranging from 2.6% to 33% recorded by several authors in a similar cohort in different regions of the world [46][47][48][49][50]. Variation in the performance of different ELISA kits employed in these studies may account for the difference in rates reported.…”
Section: Discussioncontrasting
confidence: 56%
“…Our finding, though higher than 0% rate reported in a similar cohort in France [45], is lower than rates ranging from 2.6% to 33% recorded by several authors in a similar cohort in different regions of the world [46][47][48][49][50]. Variation in the performance of different ELISA kits employed in these studies may account for the difference in rates reported.…”
Section: Discussioncontrasting
confidence: 56%
“…Reports from Africa demonstrated a rate of 12% in Tunisia (17), 14% in Gabon (18), 28% in Ghana (19), and 84% in Egypt (20) for anti-HEV seroprevalence among pregnant women. In addition, a study in Indian pregnant women showed a prevalence of 33% for anti-HEV seropositivity (21).…”
Section: Discussionmentioning
confidence: 99%
“…While there is much published literature on HEV infection during pregnancy from other African countries, 11,12 there are few published data on HEV infection during pregnancy in Sudan. 13,14 The current study was conducted to investigate the epidemiology, and maternal and perinatal outcomes of HEV infection among pregnant women at Port Sudan Hospital, Eastern Sudan to provide a better understanding of maternal and perinatal outcomes of communicable diseases in general, as well as viral hepatitis, during pregnancy in this region of Sudan.…”
mentioning
confidence: 99%